Accumulated ROS Activates HIF-1α-Induced Glycolysis and Exerts a Protective Effect on Sensory Hair Cells Against Noise-Induced Damage - Liang, Shuo; Dong, Shuohui; Liu, Wenwen; Wang, Man; Tian, Shanshan; Ai, Yu; Wang, Haibo (Frontiers in Molecular Biosciences, 2022)
Noise exposure causes noise-induced hearing loss (NIHL). NIHL exhibits loss of inner ear sensory hair cells and is often irreparable. Although oxidative stress is involved in hearing loss, the complex mechanisms involved in NIHL are unclear. Hypoxia-inducible factor 1α (HIF-1α) has been suggested to be essential for protecting sensory hair cells. Additionally, it has been shown that ROS is involved in modulating the stability of HIF-1α. To investigate the NIHL pathogenesis, we established a tert-butyl hydroperoxide (t-BHP)-induced oxidative stress damage model in hair-like HEI-OC1 cells and an NIHL model in C57BL/6 mice. Protein and mRNA expression were determined, and biochemical parameters including reactive oxygen species (ROS) accumulation, glucose uptake, adenosine triphosphat (ATP) production, and mitochondrial content were evaluated. In HEI-OC1 cells, t-BHP induced ROS accumulation and reduced mitochondrial content and oxygen consumption, but the ATP level was unaffected. Additionally, there was increased glucose uptake and lactate release along with elevated expression of HIF-1α, glucose transporter 1, and several glycolytic enzymes. Consistently, noise trauma induced oxidative stress and the expression of HIF-1α and glycolytic enzymes in mice. Thus, we concluded that ROS induced HIF-1α expression, which promoted glycolysis, suggesting a metabolic shift maintained the ATP level to attenuate hair cell damage in NIHL.